A comprehensive review of integrated energy storage batteries in renewable energy stations: technological advancements, challenges and future trends - Assia Redouani; Ghita Ikmel; Kamal Zared; Giedrius Čyras; Najiba El Amrani El Idrissi (Insights into Regional Development)
The integration of energy storage batteries into renewable energy stations is a crucial development in the quest for sustainable and reliable energy solutions. This review provides a comprehensive analysis of this integration, detailing the types of energy storage batteries, including lithium-ion, lead-acid, and flow batteries, as well as their respective benefits and limitations. The study addresses significant challenges such as the intermittency of renewable energy sources, battery degradation and lifetime, cost and efficiency issues, and technical challenges. It also explores potential solutions to these challenges. Additionally, future directions are discussed, focusing on emerging battery technologies and smart grid system integration. This paper highlights the essential role of energy storage batteries in overcoming the intermittency of renewable sources and ensuring a stable and efficient energy supply.